2010
DOI: 10.1007/s11010-010-0418-5
|View full text |Cite
|
Sign up to set email alerts
|

ROS-NFκΒ mediates TGF-β1-induced expression of urokinase-type plasminogen activator, matrix metalloproteinase-9 and cell invasion

Abstract: TGF-beta1 has been postulated as a pro-oncogenic factor in the late step of the tumoral progression. In transformed cells, TGF-beta1 enhances the capacity to degrade the extracellular matrix, cell invasiveness and epithelial-mesenchymal transition, which are crucial steps for metastasis. Urokinase-type plasminogen activator (uPA) and matrix metalloproteinase-9 (MMP-9) are critical components in cell migration and invasion induced by TGF-beta1, however, the exact mechanism by which TGF-beta1 regulates uPA and M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
126
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 157 publications
(131 citation statements)
references
References 20 publications
5
126
0
Order By: Relevance
“…This loss of BRMS1 further enhances aberrant activation of NF-B and deregulates NF-B-dependent genes. NF-B plays an essential role in the induction and maintenance of EMT in malignant epithelial cells in response to stimulation by the inflammatory cytokines TGF-␤ and TNF (12,50,51). We observed that knockdown of BRMS1 significantly magnified TGF-␤-stimulated EMT in NSCLC cells.…”
Section: Discussionmentioning
confidence: 68%
“…This loss of BRMS1 further enhances aberrant activation of NF-B and deregulates NF-B-dependent genes. NF-B plays an essential role in the induction and maintenance of EMT in malignant epithelial cells in response to stimulation by the inflammatory cytokines TGF-␤ and TNF (12,50,51). We observed that knockdown of BRMS1 significantly magnified TGF-␤-stimulated EMT in NSCLC cells.…”
Section: Discussionmentioning
confidence: 68%
“…[47][48][49] In addition, we found reduced levels of the MMP-9 mRNA. Levels of MMP-9 are elevated in invasive cells 50 ( Fig. 3A).…”
Section: Butein Affects the Resistance Of Mpm Cells To Pemetrexedmentioning
confidence: 91%
“…5A-C). In addition to control by TGF-b1 and Smad signaling, MMP-9 can be regulated by the NF-kB pathway (38,39). Accordingly, IL-1b and IL-18, alone or together, promoted the ability of TGF-b1 to induce MMP-9 expression (Fig.…”
Section: Nlrp3 Promotes Emt Independently Of the Inflammasomementioning
confidence: 96%